Multiple Response Optimization of a HPLC Method for Analyzing Resorcinol and 4-n-Butyl Resorcinol in Lipid Nanoparticles - Rini Dwiastuti; Dina Christin Ayuning Putri; Maywan Hariono; Florentinus Dika Octa Riswanto (Indonesian Journal of Chemistry, 2021)
Resorcinol and 4-n-butyl resorcinol have been used to improve skin health. However, these two compounds were unstable due to the oxidation process. Lipid nanoparticle formulation strategies were reported as the solution to overcome the stability problem for both resorcinol and 4-n-butyl resorcinol. Nevertheless, it is important to determine the content of resorcinol and 4-n-butyl resorcinol in lipid nanoparticle formulation. Aiming to develop the analytical method for resorcinol and 4-n-butyl resorcinol determination, a response surface methodology (RSM) was applied in the HPLC optimization stage. An optimized HPLC condition was obtained by generating a Box-Behnken design followed by multiple response analysis. It was obtained that optimized HPLC conditions due to the predictive multiple response optimization were methanol percentage of 50.0%, acetonitrile percentage of 18.1%, and flow rate of 0.6 mL min–1. This optimized condition was successfully applied and met the requirements of the system suitability test. Quantitative estimation was performed and resulted that the resorcinol and 4-n-butyl resorcinol content in lipid nanoparticles were 70.37 ± 0.47 and 95.07 ± 0.80 µg mL–1, respectively.